Central-Bank Independence Revisited - Fischer, Stanley (American Economic Review, 1995)
The case for central-bank independence (CBI), while not a new one, has been strengthened by a growing body of empirical evidence, by recent developments in economic theory, and by the temper of the times. The case is a strong one,1 which is becoming part of the Washington orthodoxy. The purposes of this paper are both to make more precise the type of CBI that is likely to enhance economic performance, and to point to some remaining open issues and anomalies. I start with the two theoretical approaches to CBI.